Peningkatan Hasil Belajar Siswa Pada Pembelajaran Berdiferensiasi Percobaan Listrik Kelas 5 SDN Rejosari 01 Semarang - Muslimah, Linda Ayu; Artharina, Filia Prima; Devega, Lidya Septia (Didaktika, 2024)
Students' characteristics greatly influence learning outcomes in class. Students lack concentration when doing electrical experiments in class because of monotonous learning. In addition, some students make mistakes when stacking cables and electrical components, leading to confusion and prompting them to seek assistance from friends who may not fully understand basic electrical stacking techniques. Teachers can use differentiated learning to implement strategies to improve students' learning outcomes. There are three elements: visual, auditorium, and kinesthetic. We expect students to be more concentrated with this differentiated learning approach, and with proper learning, they can perform electrical experiments correctly as the classroom learning process aligns with their learning style. The research aims to improve students' learning outcomes in 5th grade SDN Rejosari 01 Semarang Teaching Year 2023-2024 through differentiated electrical experiments. The researcher employs classroom action research (CAR) in conjunction with the PJBL method, which undergoes two cycles of differentiation involving 27 students from 5B SDN Rejosari 01. At each cycle, there is planning, implementation, observation, evaluation, and reflection. In the pre-cycle, 4 students (44.44%) showed improvements in their visual learning style, with an average score of 68.88. Cycle I became 6 students (66.67%) with an average of 77.78, and Cycle II became 8 students (88.89%) with an average of 90. Thus, the application of differentiated learning in the Electrical experiments in the fifth grade of SDN Rejosari 01 Semarang has improved the learning outcome from the target of 75. Therefore, we can conclude that this class action research is effective.